2021
DOI: 10.1186/s13063-021-05330-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial reporting performance of thirty UK universities on ClinicalTrials.gov—evaluation of a new tracking tool for the US clinical trial registry

Abstract: Clinical trial transparency forms the foundation of evidence-based medicine, and trial sponsors, especially publicly funded institutions such as universities, have an ethical and scientific responsibility to make the results of clinical trials publicly available in a timely fashion. We assessed whether the thirty UK universities receiving the most Medical Research Council funding in 2017–2018 complied with World Health Organization best practices for clinical trial reporting on the US Clinical Trial Registry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Some trials were registered on both sites and in some of these cases the full protocol was available on one site but not the other, or there was conflicting information regarding protocol versions, recruitment figures, and overall trial status (in set-up, open, closed, follow-up). Such discrepancies in trial registry information have been reported previously [36][37][38]. Some trials did not have a full protocol deposited on the registry but had links to documents on a study-specific website.…”
Section: Discussionmentioning
confidence: 80%
“…Some trials were registered on both sites and in some of these cases the full protocol was available on one site but not the other, or there was conflicting information regarding protocol versions, recruitment figures, and overall trial status (in set-up, open, closed, follow-up). Such discrepancies in trial registry information have been reported previously [36][37][38]. Some trials did not have a full protocol deposited on the registry but had links to documents on a study-specific website.…”
Section: Discussionmentioning
confidence: 80%
“…The hypothesis that political engagement drove the increase in CTIMP reporting performance on the EU Clinical Trial Register is supported by data showing that UK universities during the same time period did not extend their reporting efforts to other types of clinical trials listed on different trial registries; we found in October 2020 that only 10.2% of trials sponsored by UK universities had reported tabular summary results on the US-based ClinicalTrials.gov registry. 11 The committee’s letter only referred to CTIMPs, so universities largely focused their efforts on these trials only; also there is no regulatory requirement to upload the results of non-CTIMPs onto trial registries.…”
Section: Discussionmentioning
confidence: 99%
“…All CTIMPs conducted in the European Union must register on the EU Clinical Trial Register and upload their summary results within 12 months of completion. 4,8 In the past 3 years, we have evaluated clinical trial policies of UK universities, tracking their clinical trial registration and reporting policies as well as their reporting performance on the EU Clinical Trial Register and the American ClinicalTrials.gov trial registry [9][10][11] . This took place within the framework of the Universities Allied for Essential Medicines UK's Global Health Report Cards, 12 which evaluate the policies and performance of universities in the United Kingdom with regard to global health equity.…”
Section: Box 1what Are Ctimps?mentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, previous research indicates that many institutions' efforts to improve trial reporting did not extend to other types of trials listed on other trial registries. 3 The UK's national #MakeItPublic strategy now aims to ensure that going forward, all clinical trials involving UK patients will make their results public, but the strategy's scope does not extend retrospectively to older legacy trials. 4 Previous studies have found that in the absence of any external intervention, the results of very few trials that remain unpublished after 5 years will ever be made public.…”
mentioning
confidence: 99%